Libraries connected on Instagram: analysis of the impact and engagement of the accounts of three university libraries from Argentina - Myers, Cecilia-Ingrid (Revista de Investigación sobre Bibliotecas, Educación y Sociedad, 2024)
Libraries are institutions that renew and modernize themselves to meet the needs of people who require information and make use of their services. The development of technologies not only has changed the work in libraries but also the communication with users through, for example, social networks. The aim of this paper is to show a different perspective of the use of social networks in university libraries, investigating and analyzing how Instagram presents both similarities and opportunities with the technical, administrative and service processes of libraries to be implemented as a tool for dissemination of their services. For this purpose, a sample of the accounts of the Library of the Faculty of Exact and Natural Sciences and the Library of the Faculty of Agronomy of the University of Buenos Aires and the Library of the Torcuato Di Tella University were taken. We analyze the impact they generate, the content published and the engagement with their followers. Finally, we propose some thoughts on the relationship between Instagram and the reality of libraries due to the need for planning and interaction with users.
Keywords: Librarianship; College libraries; Social media; Instagram; Dissemination; University libraries; Academic libraries; Library services; Social networks; Impact; Interaction; Engagement